PEMANFAATAN LIMBAH SAYURAN PASAR PADA FORMULASI MEDIA PAKAN YANG BERBEDA TERHADAP KONSUMSI NUTRISI BAHAN KERING (BK), BAHAN ORGANIK (BO) DAN PROTEIN KASAR (PK) PADA ULAT JERMAN - Bangar, Putri Mbangi; Supartini, Nonok; Santoso, Erik Priyo (Universitas Tribhuwana Tunggadewi, 2017)
This study aimed to determine the utilization of market vegetables waste on different feed media formulations on the consumption of dry matter nutrients, organic matter, crude protein in German caterpillar. The experiment method was Completely Randomized Design (CRD) method with 1 factor was crude protein (CP) = 10%, 12% and 14%, factor 2 was gross energy (GE) = 4000 kcal/kg, 4500 kcal/kg dan 5000 kcal/kg. There were 9 treatments G1P1 4000 kkal/kg, CP 10%, G1P2 4000 kca CP 12%, G1P3 4000 kcal CP 14%, G2P1 4500 kcal CP 10%, G2P2 4500 kcal CP 12%, G2P3 4500 kcal CP 14%, G3P1 5000 kcal CP 10%, G3P2 5000 kcal CP 12%, G3P3 5000 kcal CP 14%. The results showed that the utilization of market vegetable waste on different feed media formulation did not give significant effect (P> 0,05) On dry matter consumption. Consumption of organic materials highest 2018,76 mg/head gave a good influence on the weight of harvest and weight gain. For gross energy 4000 kcal and crude protein 14% giving significant effect (P0,05) terhadap konsumsi bahan kering. Konsumsi bahan organik tertinggi 2018,76 mg/ekor memberikan pengaruh terhadap bobot panen dan pertambahan bobot badan. Untuk Gross Energy 4000 kkal dan protein 14% menghasilkan konsumsi protein kasar memberikan pengaruh nyata (P